Автоматизація процесів керування спеціальним технологічним обладнанням - Соколова, Яна; Таванюк, Тетяна; Азаренко, Наталія (КІНПАТРІ ЛТД, 2013)
The synthesis of automatic control system special technological equipment with electro-hydraulic drive for expansion of functionality and increasing its accuracy.
Automation of control processes special technological equipment